The Communist Transnational? Transnational studies and the history of the Comintern - Drachewych, Oleksa (History compass, 2019)
In the last decade, the historiography of international communism during the interwar period, organized by the Bolshevik-led Communist International, or Comintern, which existed from 1919 to 1943, has undergone significant shifts with one prominent new trend in the field being transnational studies. With the transnational turn, scholars have been able to reconsider how communist ideas were transmitted throughout the world, moving past traditional histories that focused either on national communist parties or the bureaucracy of the Communist International. Though transnational studies of the Comintern are still relatively new to the field, they have provided more information about communist front organizations, the lives of individual communists, and the networks in which these individuals traveled. Transnationality has also helped shift communism away from being a peripheral subject in the histories of imperialism, diaspora communities and radical networks of the interwar period to being a prominent feature of studies on these topics. In this historiographical review of transnational studies of the Comintern, it may be better to colloquially refer to the Communist International as the Communist Transnational as a historiographical frame of reference, reflecting how significant these political or cultural exchanges were across borders.